ZnO nanorod provided with orthogonal copper oxide nanosheets and corresponding gas sensor

By growing transverse copper oxide nanosheets on ZnO nanorods to form CuO nanosheets, the problem of insufficient gas sensitivity at low temperatures in existing ZnO/CuO composite materials is solved, and efficient response and selectivity to a variety of gases are achieved. Suitable for a wide range of applications.

CN119256224APending Publication Date: 2025-01-03LUXEMBOURG INSTITUTE OF SCIENCE AND TECHNOLOGY (LIST)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380042522.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-21
Filing Date
2023-04-20
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The gas sensitivity and selectivity of existing ZnO/CuO composite materials at room temperature or below 200°C are limited and need to be improved.

Method used

By growing transverse copper oxide nanosheets on ZnO nanorods, CuO nanosheets are formed, which increases the sensitivity of resistivity change of the gas sensing layer. Cu2(OH)3Cl and Cu(OH)2 are used as intermediates and converted into CuO nanosheets, optimize the arrangement of nanosheets to maximize surface contact area.

Benefits of technology

It significantly improves the sensitivity and selectivity of chemical resistance gas sensors, shows good response to gases such as O2, H2, CO, and NO2. It is suitable for gas sensing, photocatalysis and water decomposition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119256224A_ABST
    Figure CN119256224A_ABST
Patent Text Reader

Abstract

The invention relates to a metal oxide material comprising ZnO nanorods (2) and copper oxide nanosheets (4; 4 ') extending transversely to the ZnO nanorods (2). 6); a method for synthesizing the metal oxide material; and a gas sensor, the gas sensor comprising: a substrate; at least two electrodes deposited on the substrate; a gas sensing layer comprising ZnO nanorods deposited on the at least two electrodes and on the substrate between the at least two electrodes, the gas sensing layer exhibiting a resistivity that varies upon contact with a gas; wherein the ZnO nanorod is provided with a transverse CuO nanosheet so as to endow the gas sensing layer with sensitivity to gas, and the gas is at least one of O2, H2, CO, ethanol and NO2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of metal oxide heterostructures for various applications including gas sensing, photocatalysis and water splitting. Background Art

[0002] The disclosed prior art patent document CN 106814113 A discloses a semiconductor oxide gas sensor based on ZnO nanorods on which CuO particles are grown to provide good sensitivity to H2S. The CuO particles are evenly distributed on the ZnO nanorods and show a diameter between 20nm and 50nm. The resulting gas sensor shows good sensitivity to H2S and good selectivity compared to other gases such as SO2, Cl2 and O2, especially at 50°C.

[0003] The disclosed prior art patent document CN 107537501 A discloses a method for producing a ZnO / CuO composite material, which is intended for gas sensing, photocatalysis and water decomposition. The ZnO / CuO composite material includes a ZnO matrix and a flower-like hierarchical structure of CuO nanoparticles attached to the surface of the matrix. The size of the CuO nanoparticles is between 10 and 50 nm, while the size of the hierarchical structure of ZnO is between 10 and 20 μm.

[0004] Rutuja Bhusari,Jean-Sébastien Thomann, Guillot, Renaud Leturcq, "Morphology control of copper hydroxide based nanostructures in liquid phase synthesis", Journal of Crystal Growth, Volume 570, 2021, 126225, ISSN 0022-0248, https: / / doi.org / 10.1016 / j.jcrysgro.2021.126225 (https: / / www.sciencedirect.com / science / article / pii / S0022024821002001) discloses the synthesis and study of copper hydroxide based nanostructures as templates for the formation of CuO, more particularly, the template-free bottom-up synthesis and shape control of copper hydroxide based nanostructures grown in liquid phase from 1D nanowires to 2D layered nanosheets and 3D nanocrystals.

[0005] The gas sensitivity of the above-mentioned ZnO / CuO composite materials is still limited, especially at room temperature or controlled temperatures below 200° C. Therefore, it is desirable to increase the gas sensitivity and / or selectivity of these materials. Summary of the invention

[0006] Technical issues

[0007] The present invention has the technical problem of overcoming at least one of the above-mentioned disadvantages of the prior art. More specifically, the present invention has the technical problem of providing metal oxide heterostructures with increased chemiresistive gas sensitivity and / or selectivity.

[0008] Technical Solutions

[0009] The present invention relates to a gas sensor, which comprises a substrate; at least two electrodes deposited on the substrate; a gas sensing layer, which comprises ZnO nanorods deposited on the substrate on and between the at least two electrodes, the gas sensing layer showing a resistivity that changes when in contact with a gas; wherein the ZnO nanorods are provided with lateral copper oxide nanosheets so as to impart sensitivity to the gas sensing layer to a gas, the gas being at least one of O2, H2, CO, ethanol and NO2.

[0010] The copper oxide forming the lateral nanosheets includes CuO. It may also include Cu2(OH)3Cl and Cu(OH)2.

[0011] According to a preferred embodiment, the ZnO nanorods have a length between 1 and 10 μm.

[0012] According to a preferred embodiment, the ZnO nanorods have a diameter between 50 nm and 600 nm.

[0013] According to a preferred embodiment, the ZnO nanorods extend along the longitudinal axis and the lateral copper oxide nanosheets are perpendicular to the longitudinal axis within a tolerance of ±15°, preferably within a tolerance of ±10°.

[0014] According to a preferred embodiment, the ZnO nanorods provided with lateral copper oxide nanosheets have a number of 10 to 100 lateral CuO nanosheets per μm length of the ZnO nanorods.

[0015] According to a preferred embodiment, the ZnO nanorods provided with lateral copper oxide nanosheets can be obtained by the method according to any one of claims 13-18.

[0016] Advantageously, the gas sensor further comprises a resistor dimensioned for subjecting the substrate, the at least two electrodes and the gas sensing layer to a temperature of at least 100°C and up to 250°C.

[0017] The present invention also relates to a metal oxide material, comprising ZnO nanorods; and copper oxide particles attached to the ZnO nanorods; wherein the copper oxide particles are nanosheets extending transversely to the ZnO nanorods.

[0018] According to a preferred embodiment, the ZnO nanorods have a length between 1 and 10 μm.

[0019] According to a preferred embodiment, the ZnO nanorods have a diameter between 50 and 600 nm.

[0020] According to a preferred embodiment, the ZnO nanorods extend along the longitudinal axis and the lateral copper oxide nanosheets are perpendicular to the longitudinal axis within a tolerance of ±15°, preferably within a tolerance of ±10°.

[0021] According to a preferred embodiment, the ZnO nanorods provided with lateral copper oxide nanosheets have a number of 10 to 100 lateral CuO nanosheets per μm length of the ZnO nanorods.

[0022] According to a preferred embodiment, the ZnO nanorods provided with lateral copper oxide nanosheets can be obtained by the method according to any one of claims 13-18.

[0023] The present invention also relates to a method for synthesizing ZnO nanorods provided with Cu-based nanosheets, comprising the following consecutive steps: (a) preparing ZnO nanorods; (b) mixing the ZnO nanorods with a Cu precursor in a solution; (c) increasing the pH of the solution so as to form Cu(OH)2 nanowires in the solution; (d) lowering the pH of the solution so as to form Cu2(OH)3Cl nanosheets on the ZnO nanorods.

[0024] Advantageously, the solution is aqueous (water-based).

[0025] According to a preferred embodiment, the method comprises the further step of: (e) annealing the ZnO nanorods provided with Cu2(OH)3Cl nanosheets so as to at least partially convert the Cu2(OH)3Cl nanosheets into CuO nanosheets.

[0026] According to a preferred embodiment, the annealing of step (e) is carried out at a temperature of at least 100° C. for a period of at least 1 hour, preferably at least 2 hours.

[0027] According to a preferred embodiment, the annealing of step (e) is carried out at a temperature of at least 200° C. for a period of at least 1 hour, preferably at least 2 hours.

[0028] According to a preferred embodiment, step (c) comprises adding NaOH to increase the pH to at least 12.

[0029] According to a preferred embodiment, step (d) comprises adding HCl to lower the pH to a value between 6 and 8.

[0030] Advantageously, the Cu precursor comprises CuCl2.

[0031] Advantages of the present invention

[0032] Of particular interest is the present invention which provides a metal oxide material and corresponding gas sensor that exhibits improved chemiresistive sensitivity in the presence of different gases substantially by increasing the total contact surface per unit of metal oxide material with the gas.

[0033] The application range of the metal oxide material of the present invention is wide and is therefore not limited to gas sensing, and in the case of gas sensing, is not limited to sensing a unique or specific type of gas. The working principle of a chemiresistive gas sensor is the change in resistance due to a chemical redox reaction and is based on Ohm's law V=R·I. When the target gas interacts with the adsorbed oxygen or with elements on the surface of the chemiresistive sensor, a reaction occurs. This results in a change in the resistance of the material. The ability of the metal oxide surface to react with the target gas depends on the properties of the surface and the oxygen species adsorbed on the surface. The adsorption of oxygen on the surface changes the resistance of the semiconductor material formed by the metal oxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 A heterostructure of ZnO nanorods with lateral CuO nanosheets according to the present invention is shown.

[0035] Figure 2 The synthesis of ZnO nanorods with lateral Cu2(OH)3Cl nanosheets according to the present invention is shown.

[0036] Figure 3 The geometry of the nanoparticles relative to the nanosheets is shown.

[0037] Figure 4 A gas sensor according to the invention is shown according to two variants.

[0038] Figure 5 Graph showing the electrical behavior of a gas sensor according to the invention in contact with various gases. DETAILED DESCRIPTION

[0039] Figure 1 A heterostructure of ZnO nanorods provided with lateral CuO nanosheets according to the present invention is shown.

[0040] It is apparent that ZnO nanorods 2 and Cu2(OH)3Cl nanosheets 4 grown on the ZnO nanorods 2 are provided. The ZnO nanorods 2 with the Cu2(OH)3Cl nanosheets 4 are then annealed, resulting in the conversion of the Cu2(OH)3Cl nanosheets 4 into CuO nanosheets 6.

[0041] It is evident that the nanosheets of Cu2(OH)3Cl nanosheets 4 and more particularly CuO nanosheets 6 are perpendicular to the longitudinal axis of the ZnO nanorods 2 and are evenly distributed along and around the nanorods 2. This particular arrangement of CuO nanosheets on the ZnO nanorods is particularly advantageous because it maximizes the effective surface of the copper oxide nanosheets per nanorod, thereby increasing the catalytic effect available for various applications including gas sensing, photocatalysis, and water splitting.

[0042] Figure 2 A method for synthesizing the above-mentioned ZnO nanorods 2 with Cu2(OH)3Cl nanosheets 4 is shown.

[0043] More specifically, Figure 2 Part a) shows the synthesis of ZnO nanorods, comprising essentially mixing ZnCl2 with hexamethylenetetramine (HTMA) (also known as methenamine, hexamine or urotropin, and a heterocyclic organic compound having the formula (CH2)6N4) with water, heating and mixing, and centrifuging. More specifically, the method comprises the following steps:

[0044] -like Figure 2 As shown in part a)-1 of the present invention, a solution, such as water, is provided, and the solution is heated, for example, to a temperature between 50°C and 100°C, preferably between 60°C and 80°C;

[0045] -like Figure 2 As shown in part a)-2, ZnCl2 and hexamethylenetetramine (HTMA) (preferably in equimolar amounts) are added and dissolved into the solution while the solution is kept heated;

[0046] -like Figure 2 As shown in part a)-3 of the present invention, the above solutions are mixed while heating the solutions preferably at a slightly higher temperature between 70 and 100° C., and this is during a certain duration, for example, a duration of at least 60 minutes;

[0047] -like Figure 2 As shown in part a)-4 of the present invention, the solution is centrifuged while stopping heating, for example at room temperature, so as to separate the ZnO nanorods from the solution.

[0048] like Figure 2As shown in part a)-5 of , the centrifuged ZnO nanorods can be added to a solvent solution (such as ethanol), optionally together with CuCl2, in preparation for an additional step of growing copper oxide on the ZnO nanorods.

[0049] The above-mentioned method for synthesizing ZnO nanorods is known per se, in particular from patent application WO 2019 / 057786 A1 assigned to the applicant of the present application. Other methods are also conceivable.

[0050] Figure 2 Part b) shows the growth of Cu2(OH)3Cl nanosheets on the ZnO nanorods synthesized above. It should be understood that the ZnO nanorods do not necessarily need to be grown according to the method described above. Figure 2 The above method was shown in part a) of the synthesis.

[0051] As in Figure 2 As evident in part b), a solution of ZnO nanorods and a copper precursor (such as CuCl2) in a solution (e.g. water) is mixed with ammonia NH4OH and sodium hydroxide NaOH, preferably at room temperature, to increase the pH of the resulting solution, for example to at least 12. This results in obtaining a precipitate having Cu(OH)2 nanowires and ZnO nanorods.

[0052] Thereafter, the solution is heated, preferably between 60° C. and 80° C., and the pH of the solution is lowered by adding an acid, such as hydrochloric acid HCl, to a value not greater than 8 and greater than 5, preferably between 6 and 7.5, wherein botallackite (Cu2(OH)3Cl) nanosheets are formed. Lowering the pH to lower values ​​will form undesirable clinoatacamite (Cu2(OH)3Cl) nanocrystals.

[0053] The obtained ZnO nanorods with Cu2(OH)3Cl nanosheets were Figure 2 c) of the embodiment of the present invention. The solution can then be centrifuged and washed to separate the ZnO nanorods with Cu2(OH)3Cl nanosheets, which can then be applied to a substrate to form a gas sensor, a photocatalyst, and a water separator. Alternatively, the ZnO nanorods with Cu2(OH)3Cl nanosheets can be stored in a solvent such as ethanol.

[0054] As above combined Figure 1 The ZnO nanorods with Cu2(OH)3Cl nanosheets are annealed to convert the Cu2(OH)3Cl nanosheets into CuO nanosheets. The annealing is performed at a temperature between 100 and 400°C for at least one hour, preferably at least two hours.

[0055] The conversion of Cu2(OH)3Cl nanosheets into CuO nanosheets and the conversion of Cu 2p 3 / 2 The peak after annealing shows a substantially higher peak in the atomic count corresponding to the binding energy of 933.6 eV of CuO than before annealing. There is also the presence of Cu2(OH)3Cl or Cu(OH)2, as evidenced by the peak at the binding energy of 934.8 eV, where the peak height decreases after annealing compared to before annealing. As an example, the mass ratio between Cu in CuO and Cu in copper hydroxide (Cu2(OH)3Cl or Cu(OH)2) is determined by XPS Cu 2p 3 / 2 The peaks were evaluated by fitting and found to be 0.5 before annealing and 2.5 after annealing at 400 °C for 2 hours.

[0056] The conversion of Cu2(OH)3Cl nanosheets into CuO nanosheets has also been confirmed by X-ray diffraction analysis (XRD) of the sample, wherein the peak at an angle of 15.5 degrees corresponding to chlorotacamite Cu2(OH)3Cl, the peak at an angle of 16.7 degrees corresponding to paratacamite Cu2(OH)3Cl, and the peaks at angles of 16.2 and 23.8 degrees corresponding to Cu(OH)2 are suppressed after annealing, and the peaks at angles of 35.5 and 38.9 degrees corresponding to CuO appear after annealing.

[0057] The conversion of Cu2(OH)3Cl nanosheets into CuO nanosheets also changes the optical properties of the composite material. For example, absorbance analysis of the samples in the wavelength range of 250nm to 1500nm has been performed and revealed that the annealed composite material shows substantially higher absorbance in the visible light range (300 to 800nm), and the absorbance of the samples annealed at higher temperatures is higher than those annealed at lower temperatures, which are between 100°C and 400°C.

[0058] Figure 3 The geometry of the nanoparticles relative to the nanosheets is shown.

[0059] The upper left figure shows a droplet or particle-shaped element attached to a support, and the lower left figure shows an array arrangement of the droplet or particle-shaped element. The upper right figure shows a sheet-shaped element attached to a support, and the lower right figure shows an evenly distributed arrangement of the sheet-shaped element on the support.

[0060] For droplet or particle shaped components, we have

[0061]

[0062] Where R is the radius of the droplet or particle-shaped element, P and A are the circumference and surface of the droplet or particle-shaped element on the support, respectively. Thus, a droplet or particle-shaped element of nanometer radius will show a surface that is proportionally reduced compared to the circumference (i.e. the area it occupies on the substrate).

[0063] If we consider the above array of droplet or particle-shaped elements, we have

[0064]

[0065]

[0066] Where R is the radius of the droplet or particle-shaped element, P 总 and A 总 is the total perimeter and total covered surface of the droplet or particle-shaped element, and d is the distance between directly adjacent droplets or particle-shaped elements. Thus, an array of droplet or particle-shaped elements will show a total perimeter that is the sum of the perimeters of all droplets or particle-shaped elements of the array, which represents the active surface that can be contacted by the gas, which will gradually become smaller than the total surface occupied by the droplet or particle-shaped element on the substrate as the radius R of the droplet or particle-shaped element reaches the nanometer scale.

[0067] For sheet elements, we have

[0068]

[0069]

[0070] P=2L+2w

[0071]

[0072] Where L is the length of the sheet-shaped element and w is the width (actually the thickness) of the sheet-shaped element, P and A are respectively the perimeter and the surface of the sheet-shaped element on the support. Thus, a sheet-shaped element of nanometer width w will maintain a perimeter proportional to its length L, while the space it occupies on the substrate is reduced.

[0073] If we consider the above uniform distribution of the sheet-shaped elements, we have

[0074]

[0075]

[0076] Where P 总 and A 总is the total perimeter and the total covered surface of the sheet-shaped elements, and d is the distance between directly adjacent sheet-shaped elements. Thus, reducing the width w to the nanometer scale allows a fixed ratio to be maintained between the total perimeter representing the active surface accessible to the gas and the total surface on the support occupied by the sheet-shaped elements.

[0077] The above demonstrates the advantage of the above described lateral arrangement of copper oxide nanosheets on ZnO nanorods in terms of optimizing the total contact surface with the ambient gas for a given number and size of nanorods. This therefore optimizes the sensitivity of the composite material.

[0078] The ZnO nanorods may have a length between 1 and 10 μm and a diameter between 50 and 600 nm, resulting in a form factor between 1.7 and 200. The lateral copper oxide nanosheets may be distributed along the length of the ZnO nanorods at a density of 10 to 100 per μm. The lateral copper oxide nanosheets may have a thickness between 15 and 35 nm (corresponding to Figure 3 The length (corresponding to Figure 3 The L in the figure can be between 800 and 2300 nm, and the height (perpendicular to Figure 3 The w and L in ( ) may be between 300 and 630 nm. The above ranges are also disclosed independently of each other, and each range is disclosed only with its lower limit and also only with its upper limit.

[0079] Moreover, the above-mentioned lateral copper oxide nanosheets are transverse to the ZnO nanorods, preferably have a normal parallel to the longitudinal axis of the ZnO nanorods or are inclined no more than 45° relative to the longitudinal axis, more preferably are perpendicular to the ZnO nanorods within a tolerance of ±15°, and even more preferably are perpendicular to the ZnO nanorods within a tolerance of ±10°.

[0080] Furthermore, the above-mentioned ZnO nanorods show a polygonal cross section, forming a surface on which the lateral copper oxide nanosheets are attached.

[0081] Figure 4 Two embodiments of a gas sensor according to the invention are shown.

[0082] The first embodiment is a gas sensor 8, which includes a substrate 10, a first electrode 12 and a first contact area electrically connected to the first electrode 12. Similarly, the gas sensor includes a second electrode 16 and a second contact area electrically connected to the second electrode 12. It is obvious that the first electrode 12 and the second electrode 16 are interdigitated. The first electrode 12 and the second electrode 16 and the first contact area 14 and the second contact area 18 are formed by depositing a conductive material (e.g., a copper base) on the substrate 10. The first electrode 12 and the second electrode 16 and the directly adjacent area of ​​the substrate 10 are covered by a layer of ZnO nanorods with lateral CuO nanosheets as detailed above, thereby forming a gas sensing layer 20.

[0083] The second embodiment is a gas sensor 108 similar to the gas sensor 8 of the first embodiment, however wherein the first and second electrodes 112 and 116 are not interdigitated. Similar to the first embodiment, the first and second electrodes 112 and 116 and the immediately adjacent areas of the substrate 110 are covered by the gas sensing layer 20.

[0084] The gas sensors 8 and 108 may further include resistor dimensions for subjecting the substrate, at least two electrodes, and the gas sensing layer to a temperature of at least 100°C and up to 250°C.

[0085] Figure 5 is a graph showing the electrical behavior of a gas sensor according to the present invention in contact with various gases.

[0086] The above gas sensor has been tested in contact with various gases and its electrical behavior has been observed and reported in Figure 5 . A power source (e.g. a voltage source) has been electrically connected to the contact areas of the gas sensor, while bringing its gas sensing layer into contact with N2 and keeping the gas sensor at a controlled temperature of 150°C, resulting in a stable nominal current I0 flowing through the gas sensor. The gas sensor is then contacted with different types of gases as will be explained below, and the current I is measured. To this end, the ambient atmosphere of the gas sensor is continuously saturated with each of the different types at a given concentration.

[0087] In practice, the gas sensor is located in a generally closed chamber, which is supplied with pure N2 and then with the gas to be measured, in the case where the gas to be measured is O2, or with dry air and then with the gas to be measured, in the case where the gas to be measured is H2, CO, NO2 or ethanol. The chamber comprises at least one exhaust port to allow the gas to be measured to flow, i.e. to be renewed in the chamber, for example approximately every 30 seconds.

[0088] The gas sensor was exposed to O2 at a mixed N2 concentration of 20.9% as a carrier gas during 1800 seconds (i.e. 30 minutes). We can observe a rapid increase in the current response, with I / I0 reaching 2 after about 600-700 seconds. Thereafter, the increase in the current response is not too steep. After applying the above-mentioned gas containing O2, for example during 1800 seconds, pure N2 was applied as before applying the O2 containing gas. We can see a rapid decrease in the current response.

[0089] Similar to the above O2 and N2 gas mixture, the gas sensor was also exposed to 2% H2 in N2 during 1800 seconds. We can observe a current response opposite to that with O2, i.e., the current decreases instead of increases. The current response I / I0 reaches 0.6 after about 750 seconds, which is comparable to the above current response through O2.

[0090] Similar to the O2-N2 and H2-N2 gas mixtures described above, the gas sensor was also exposed to 20 ppm of CO in air during 1800 seconds. The response observed for CO was very different from that observed for H2, even though both are reducing gases.

[0091] Similar to the above gas mixture, the gas sensor was also exposed to 8.26 ppm NO2 in air during 1800 seconds. We can observe a substantial increase in the current response. The delayed response observed with this gas is an experimental artifact caused by the large dilution of this particular gas. After stopping the application of the above gas mixture, a rapid decrease in the current response can be observed.

[0092] Similar to the above gas mixture, the gas sensor was also exposed to 100 ppm of ethanol (ETH) in air during 1800 seconds. We can observe a current response similar to that of H2 in N2, i.e., a decrease in the current response, while after applying the above test gas mixture, the recovery current behavior is completely different from that of H2 in N2.

[0093] In short, we are Figure 5 Good sensitivity and selectivity to the test gases were observed, thereby demonstrating the applicability and capability of the composite materials and corresponding sensors of the present invention for gas sensing applications, in particular for the above-mentioned test gases.

Claims

1. A gas sensor (8; 108), comprising: Base (10; 110); at least two electrodes (12, 16; 112, 116) deposited on the substrate; a gas sensing layer (20) comprising ZnO nanorods (2) deposited on the substrate (10; 110) on and between the at least two electrodes (12, 16; 112, 116), the gas sensing layer (20) exhibiting a resistivity that changes when contacted by a gas; It is characterized in that The ZnO nanorods (2) are provided with lateral copper oxide nanosheets (4; 6) so as to impart sensitivity to the gas sensing layer to the gas, which is at least one of O2, H2, CO, ethanol and NO2.

2. The gas sensor (8; 108) according to claim 1, wherein the ZnO nanorods (2) have a length between 1 and 10 μm.

3. The gas sensor (8; 108) according to one of claims 1 and 2, wherein the ZnO nanorods (2) have a diameter between 50 and 600 nm.

4. A gas sensor (8; 108) according to any one of claims 1 to 3, wherein the ZnO nanorods (2) extend along a longitudinal axis and the lateral copper oxide nanosheets (6) are perpendicular to the longitudinal axis within a tolerance of ±15°, preferably within a tolerance of ±10°.

5. The gas sensor (8; 108) according to any one of claims 1 to 4, wherein the ZnO nanorods (2) provided with lateral copper oxide nanosheets (4; 6) have a number of between 10 and 100 lateral copper oxide nanosheets per μm length of the ZnO nanorods.

6. The gas sensor (8; 108) according to any one of claims 1 to 4, wherein the ZnO nanorods (2) provided with lateral copper oxide nanosheets (4; 6) are obtainable by the method according to any one of claims 13 to 18.

7. A metal oxide material comprising: ZnO nanorods (2); and Copper oxide particles attached to the ZnO nanorods (2); It is characterized in that The copper oxide particles (6) are nanosheets extending transversely to the ZnO nanorods, and the transverse copper oxide nanosheets have a normal line parallel to the longitudinal axis of the ZnO nanorods or inclined at no more than 45° relative to the longitudinal axis.

8. The metal oxide material according to claim 7, wherein the ZnO nanorods (2) have a length between 1 and 10 μm.

9. The metal oxide material according to one of claims 7 and 8, wherein the ZnO nanorods (2) have a diameter between 50 and 600 nm.

10. The metal oxide material according to any one of claims 7 to 9, wherein the lateral copper oxide nanosheets (6) are perpendicular to the longitudinal axis of the ZnO nanorods within a tolerance of ±15°, preferably within a tolerance of ±10°.

11. The metal oxide material according to any one of claims 7 to 10, wherein the ZnO nanorods (2) provided with lateral copper oxide nanosheets (4; 6) have a number of between 10 and 100 lateral copper oxide nanosheets per μm length of the ZnO nanorods.

12. The metal oxide material according to any one of claims 7 to 11, wherein the ZnO nanorods (2) provided with lateral copper oxide nanosheets (4; 6) are obtainable by a method according to any one of claims 13 to 18.

13. A method for synthesizing ZnO nanorods provided with Cu-based nanosheets, comprising the following consecutive steps: (a) Preparation of ZnO nanorods; (b) mixing the ZnO nanorods and the Cu precursor in a solution; (c) increasing the pH of the solution to form Cu(OH)2 nanowires in the solution; (d) lowering the pH of the solution to form Cu2(OH)3Cl nanosheets (4) on the ZnO nanorods (2).

14. The method according to claim 13, comprising the following further steps: (e) annealing the ZnO nanorods (2) provided with the Cu2(OH)3Cl nanosheets (4) so ​​as to at least partially convert the Cu2(OH)3Cl nanosheets (4) into CuO nanosheets (6).

15. The method according to claim 14, wherein the annealing of step (e) is achieved at a temperature of at least 100°C for a period of at least 1 hour, preferably at least 2 hours.

16. The method according to claim 14, wherein the annealing of step (e) is achieved at a temperature of at least 200°C for a period of at least 1 hour, preferably at least 2 hours.

17. The method of any one of claims 13 to 16, wherein step (c) comprises adding NaOH to increase the pH to at least 12.

18. The process according to any one of claims 13 to 17, wherein step (d) comprises adding HCl to lower the pH to a value between 6 and 8.